(untitled) (Quaestiones Disputatae: temas en debate, 2019)
The way the student organization is managed in the Salamanca Technical Educational Institution, Rama Blanca Branch, Samacá municipality, is analyzed within different performance areas: family, school groups, individual, academic, behavioral, and how from there they respond to the budgets established within the Constructivist Pedagogical Model (Piaget, Vygotsky, Ausubel), with the emphasis implemented in the Institution: Teaching for Understanding (Gardner, Stone Wiske, Blythe, 1998), in the search for contributions that students can make to improve the education offered in that establishment; Likewise, we observe the way in which this pedagogical model should be evidenced in the daily life of students and presented as Student Culture, socially constructed through different interactions in the exercise of acquired knowledge, with the purpose of integrating reality through mobilization of didactic mechanisms proposed by students’ initiative in the practice of their understanding.